Hubungan Pemahaman dan Harapan Orang Tua dengan Pembelajaran Berbasis Proyek Ditinjau dari Usia dan Status Pendidikan - Indrawati, Elly; Raharjo, Tri Joko; Formen, Ali (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Parent’s profile is important in early childhood development. The purposes this research were to analyze acorrelation 1) parents’ understanding with PjBL; 2) parents’ understanding with PjBL in view of parents’ age 3) parents’ expectation with PjBL; 4) parents’ expectation with PjBL in view of parents’ age; 5) parents’ understanding and expectation with PjBL; 6) parents’ understanding and expectation with PjBL in view of parents’ education status. Quantitative method used in this research.The results of this research: 1) There is a correlation between parents’ understanding with project based learning with value 0,531; 2) There is a correlation between parents’ understanding with project based learning in view of parents’ age with value 0,532; 3) There is a correlation between parents’ expectation with  PjBL with value 0,513; 4) There is a correlation between parents’ expectation with project based learning in view of parents’ age with value 0,510; 5) There is a correlation between parents’ understanding and expectation with PjBL with value 0,668; 6) There is a correlation between parents’ understanding and expectation with PjBL in view of parents’ education status with value 0,794. The conclusion of this research was profile influenced project based learning in kindergarten.